Study on Ni2Al3 Intermetallic Compound Coating Prepared by Low Pressure Cold Spraying and Heat Treatment and Its Sliding Wear Performance - LIU Zhi-kai, SHEN Geng-zhe, LIU Can-sen, ZHANG Liu-yan, ZHENG Zhi-dong, LIU Kai-yi, JIE Xiao-hua (Cailiao Baohu, 2023)
For preparing an intermetallic compound coating with Ni2Al3 as the main phase，the Ni，Al and Al2O3 powders were mixed uniformly based on a mass ration of 20 ∶6 ∶5，and the mixed powders were sprayed onto the 45 steel surface to form a Ni-Al pre-coating by low pressure cold spraying method.Subsequently，the Ni-Al pre-coating was kept in an argon atmosphere at 520 ℃for 12 h.The morphology and phase structure of the as-prepared coating were analyzed and characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM).In addition，the bonding force as well as the sliding friction and wear performances of the coating were tested.Results showed that after thermal treatment，the pre-coating changed into a Ni2Al3 intermetallic compound coating，which presented superior anti-friction and wear-resisting properties.The driving force for the transformation of Ni and Al solid phases into intermetallic compound was the combined effect of thermal energy provided by heat treatment and deformation energy of the powders resulting from strong plastic deformation.